Modern Trends of Information Technology and Libraries in the Use of Artificial Intelligence and its Role in Applying Statistical Methods (Al-Mansour Journal, 2025)
This study focuses on the use of artificial intelligence (AI) in information and libraries, highlighting recent trends in this field and the role of statistical processing. The study aims to improve information management and retrieval by applying AI techniques for content analysis, classification, and personalized recommendations for users.Libraries and information sources pose a significant challenge for users in finding relevant information due to the vast amount and complexity of data. By employing AI techniques, the search process and information filtering can be enhanced through automated analysis and classification of content, thereby improving the user experience and increasing operational efficiency. Statistical processing plays a crucial role in this context, as it enables data analysis, pattern recognition, and trend identification. The integration of AI with statistical processing enhances the quality of analysis and the accuracy of extracted results. However, this field faces several challenges. For instance, fully leveraging AI and statistical processing requires a considerable amount of high-quality data. Advanced machine learning models need to be developed to analyze and classify diverse and complex content effectively. Additionally, addressing data security and privacy issues related to sensitive data is essential to ensure its integrity and confidential use.as a result, exploring recent trends in the use of AI in information and libraries and the role of statistical processing requires a focus on developing and improving analysis and classification techniques, as well as providing suitable infrastructure to effectively and reliably handle the growing volume of data. The research aims to achieve advancements in information management and retrieval using AI techniques and statistical processing in the context of information and libraries.
Keywords: Artificial intelligence(AI),Content analysis,Statistical processing,Information Technology,Trend identification &information management